Growing E. coli to high cell density—A historical perspective on method development - Shiloach, Joseph; Fass, Rephael (Biotechnology advances, 2005)
E. coli is the major bacterial platform for expressing simple heterologous proteins. Growing E. coli to high densities has been the subject of numerous studies since the early 1970s, exploring the limits of bacterial culture density in order to achieve maximum productivity. Research strategies were focused on improving the cultivation techniques, manipulating the bacteria's physiology or both. As a result, batch, fed batch and dialysis fermentation techniques had been developed. These growth strategies, together with optimization of media composition and the application of molecular biology methods, made it possible to grow E. coli to cell densities of up to 190 g/l (dry weight), while avoiding media precipitation and preventing acetate accumulation. Additional research on the effects of heterologous protein biosynthesis on signal transduction, proteolysis and post transcription events in E. coli may improve its productivity.